Culture and Molecular Detection of Staphylococcus aureus in Dairy Products of Ahwaz - Mastafa Heilo Jabber Al-musawi; Mushtaq Talib Shawi Al-Rubaye; Maryam Hosseini (College of Pharmacy / Mustansiriyah University, 2014)
Staphylococcus aureus is one of the most important bacteria that cause food poisoning and disease in humans and herds. Milk and milk products are important part of the human diet also support the growth of pathogenic organisms. The present study was aimed to determine the prevalence of coagulase positive Staphylococcus aureus in different kinds of dairy products of Ahvaz Province. 460 dairy product samples randomly were collected from Ahvaz Province. The samples were analyzed for the presence of S. aureus. Positive samples screened by microbiological tests. DNA extracted from all isolates and the PCR carried out using specific primers for S. aureus. The results indicated that 127 (27.61%) of dairy samples were contaminated by Staphylococcus aureus (curd 24.5%, dough 19%, butter and cream 14.5%, yogurt 12.5%, cheese 10%, milk 5%). High prevalence of Staphylococcus aureus contamination in milk and milk products of Ahvaz suggests that more control measures should be applied during dairy production. The obtained results are useful for designing strategic plans of prevention and control program against Staph. aureus in dairy ecosystem.